Isolation and Characterization of Cellulose from Underexploited Golden Melon Skin - Adewuyi, Adewale; Pereira, Fabiano Vargas (UI Scholars Hub, 2018)
Golden melon skin (GM) is an underexploited plant resource in Nigeria from which cellulose (GMC) was isolated and characterized. Characterization was achieved using Fourier transform-infrared (FT-IR) spectroscopy, X-ray diffraction (XRD), thermogravimetric analysis, and scanning electron microscopy. GMC was further evaluated for its water holding capacity (WC), oil holding capacity (OC), water swelling capacity (SC), and heavy metal adsorption capacity. FT-IR spectroscopy revealed peaks correspondingto GMC, while the XRD diffraction planes exhibited by GMC were typical of cellulose I crystals with a crystallinity index of 40%. The thermal degradation of GMC revealed a first mass loss at 190–295 °C, second loss at 305–410 °C, and third loss 285–430 °C. The WC was 11.62 g/g, OC was 2.75 mL/g, and SC was 9.32 mL/g. The heavy metal adsorption capacity of GMC toward Cu (II) was 34.52 mg/g, and it was 28.73 mg/g toward Pb (II) in an aqueous solution.These results show that GMis a potential source of cellulose, which might have useful applications.